Ganglioside Monosialic Acid Alleviates Peripheral Neuropathy Induced by Utidelone Plus Capecitabine in Metastatic Breast Cancer From a Phase III Clinical Trial - Xu, Junnan; Wang, Yan; Jiang, Cui; Cao, Hui; Jiang, Junhan; Xu, Binghe; Sun, Tao (Frontiers in Oncology, 2020)
Background: In BG01-1323L trial, utidelone, a novel genetically engineered epothilone analogue, combined with capecitabine improved progression-free survival and overall survival in heavily pretreated metastatic breast cancer prior to anthracycline and taxane. Chemotherapy-induced peripheral neurotoxicity (CIPN) was the most common dose-limiting toxicity of utidelone plus capecitabine. This study aimed to assess the efficacy of utidelone plus capecitabine in our centre and predictive role of mutations for CIPN, further to identify whether Ganglioside monosialic acid (GM1) improved CIPN. Methods: Fifty-five eligible female patients with metastatic breast cancer refractory to anthracycline and taxane were enrolled in our single centre in Phase 3 BG01-1323L trial. We randomly assigned to 39 cases in utidelone plus capecitabine and 16 cases in capecitabine alone. Progression-free survival and overall survival were assessed. Drug exposure and CIPN ratio were analyzed and SNP of enzymes and susceptible genes were detected in germline panel by NGS. Results: In our single centre, median progression-free survival in the utidelone plus capecitabine group was 238 days compared with 189 days in the capecitabine alone group, P=0.263. Median overall survival improved in combined therapy (20.9 months vs. 12.9 months, HR=0.69; 95% CI, 0.37 to 1.30; P = 0.326). The median time to the serious reported CIPN were 29 day in Grade 1, 49 day in Grade 2, 103 day in Grade 3. The median improvement time were 77 day in Grade 1, 20 day in Grade 2, 13 day in Grade 3. In combined group, 19 patients with G2 or G3 CIPN were assigned to the GM1 group and 9 patients to the control group. After intervention, the GM1 group reported demonstrated a statistically lower incidence of grade 3 CIPN [GM1 group: 1 of 19 (5.3%); Control group: 4 of 9(44.4%), P=0.026]. No associated germline SNP was found between Grade 3 and Grade 1 CIPN. Conclusions: Utidelone plus capecitabine was more efficacious compared with capecitabine alone for progression-free survival with mild toxicity except for CIPN, less grade 3 CIPN was assessed in our single centre with GM1 intervention, further investigation need to validate manageable efficacy of GM1 in CIPN in patients with utidelone plus capecitabine.